Design of Hydraulic Puller for Releasing Crankshaft Bearings on Motorcycle - Junggie Guko Armfirst; Arasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2019)
The bearing puller on the market today still has a way of working using a gripper with a screw working system. The time required is relatively long and can allow damage to the crankshaft during the bearing release process as well as reduced work performance of the crankshaft. This study aims to design a tool that works with a hydraulic system to release crankshaft motorbike bearings. This tool makes it easy for everyone to do the job of removing bearings. The outer bearing hydraulic tracker or puller uses the working principle of the lever that is pumped with calculated pressure and load and the fluid pressure on the tracker can be known ie at 1X the tracker pump requires 41 kg / cm2 fluid pressure, 2X fluid pressure tracker pump 45 kg / cm2 and 3X pump tracker requires 72 kg / cm2 fluid pressure. As well as the time needed to remove the crankshaft bearing motor especially on the A and B motorbike. To release the crankshaft bearing A motor takes 19.78 s and removing the crankshaft bearing the B motor takes 31.95 s.